Selectfluor-mediated construction of 3-arylselenenyl and 3, 4-bisarylselenenyl spiro[4.5]trienones via cascade annulation of N-phenylpropiolamides with diselenides. (4th May 2022) - Yuan, Jin-Wei; Chen, Qian; Wu, Wen-Tao; Zhao, Jian-Jun; Yang, Liang-Ru; Xiao, Yong-Mei; Mao, Pu; Qu, Ling-Bo
Abstract : A cascade annulation of N -phenylpropiolamides with diselenides leading to the construction of 3-arylselenenyl spiro[4.5]trienones was realized under mild conditions with Selectfluor as the sole oxidant. Abstract : A cascade annulation of terminal alkynyl amides with diselenides leading to the construction of 3-arylselenenyl spiro[4.5]trienones was realized under mild conditions with Selectfluor as the sole oxidant. Furthermore, 3, 4-bisarylselenenyl spiro[4.5]trienones were also synthesized by a cascade annulation reaction using transition-metal copper as a catalyst. This spirocyclization process is suggested to encompass a sequential C(sp)–Se and C(sp)–C(sp 2 ) bond formation with the concomitant introduction of a carbonyl oxygen.